2011
DOI: 10.1074/jbc.m110.211946
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the CLP/HSP100 Chaperone System from Chloroplasts of Arabidopsis thaliana

Abstract: HSP100 proteins are molecular chaperones involved in protein quality control. They assist in protein (un)folding, prevent aggregation, and are thought to participate in precursor translocation across membranes. Caseinolytic proteins ClpC and ClpD from plant chloroplasts belong to the HSP100 family. Their role has hitherto been investigated by means of physiological studies and reverse genetics. In the present work, we employed an in vitro approach to delve into the structural and functional characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
0
46
0
2
Order By: Relevance
“…Apart from its presumed involvement in Clp proteolysis, ClpC has also been implicated in the chloroplast import of cytosolic preproteins by its close proximity to Tic110, one of the principle subunits of the Tic complex (Translocon at the inner envelope membrane) (30,31). This together with the finding that ClpC stably binds transit peptides in vitro (32) has suggested that it might function as the driving force for preprotein import through the Tic complex (33). Despite this, evidence for the direct involvement of ClpC in preprotein import and processing in chloroplasts remains elusive.…”
mentioning
confidence: 83%
“…Apart from its presumed involvement in Clp proteolysis, ClpC has also been implicated in the chloroplast import of cytosolic preproteins by its close proximity to Tic110, one of the principle subunits of the Tic complex (Translocon at the inner envelope membrane) (30,31). This together with the finding that ClpC stably binds transit peptides in vitro (32) has suggested that it might function as the driving force for preprotein import through the Tic complex (33). Despite this, evidence for the direct involvement of ClpC in preprotein import and processing in chloroplasts remains elusive.…”
mentioning
confidence: 83%
“…At the inner membrane, the TPs that emerge from the Tic translocon bind directly to Tic110 (Chou et al, 2006;Tsai et al, 2013). The TPs released from Tic110 by the action of Tic40 interact with several stromal chaperones, such as Heat shock cognate70 (Hsc70), Hsp93, and possibly Hsp90C, during or after translocation (Shi and Theg, 2010;Su and Li, 2010;Rosano et al, 2011;Chotewutmontri et al, 2012;Inoue et al, 2013;Liu et al, 2014). Cytosolic factors, such as 14-3-3 and Hsp70, also bind to specific sites in the TP and facilitate import into chloroplasts (May and Soll, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutated Clp chaperone that is defective in protease core interaction fails to import proteins efficiently despite its normal envelope association (Flores-Pérez et al, 2016). Clp chaperones have the intrinsic ability to bind the N-terminal transit peptide as well as to renature nonnative proteins (Rosano et al, 2011;Bruch et al, 2012). ClpC interactions with the transit peptide and mature regions of preproteins being imported were detected recently (Huang et al, 2016).…”
Section: Quality Control Of Protein Import By Clpmentioning
confidence: 99%
“…The ClpC/D structure consists of an N-terminal region called the N domain as a substrate/adaptor docking site, two ATPase domains involved in substrate unfolding and translocation into the core, and an IGF motif (for Ile-Gly-Phe) and an R motif (named for its characteristic Arg residue), both required for core docking, with ClpC but not ClpD containing a uvrB/C motif of unassigned function . ClpC/D can recognize substrates directly (Rosano et al, 2011;Bruch et al, 2012;Huang et al, 2016), although recognition of a subset of proteins is mediated by a dedicated binary adaptor consisting of ClpS1 and ClpF (Nishimura et al, 2013. The basic ClpS structure has an N-terminal extension for substrate delivery to the chaperone and a C-terminal core domain for substrate recognition and chaperone binding Zeth et al, 2002;Erbse et al, 2006;Rivera-Rivera et al, 2014).…”
Section: Clpmentioning
confidence: 99%